Reducing Disaster Risks from Natural Hazards : An Evaluation of the World Bank’s Support, Fiscal Years 2010–20 - Independent Evaluation Group (World Bank, Washington, DC, 2022)
Disasters caused by natural hazards are increasingly threatening the lives and livelihoods of the world’s poor and disaster-vulnerable populations. Climate change is further exacerbating the negative impacts of disasters caused by natural hazards. Investing in disaster risk reduction (DRR) has strong economic and social benefits and is essential for achieving climate change adaptation. IEG's evaluation shows that the World Bank is successfully supporting clients to increasingly take up DRR actions through strategic and comprehensive country engagement. The World Bank has developed an extensive portfolio of DRR activities, tripling its support over FY10-20. It focuses its DRR work on countries with the most serious natural hazards, uses synergistic pillars of DRR engagement, and increasingly mainstreams DRR into sector operations. Support for DRR in IDA, small island developing states, and IDA-FCV countries has been comprehensive. The Bank has also shifted from post-disaster response toward pre-disaster risk reduction. The Bank has shown that it is able to overcome political and financial constraints to DRR client uptake by engaging the right decision makers using rigorous evidence and by building on disaster reconstruction efforts. Analytical work that quantified risks, assessed costs and benefits and communicates impacts has highly influenced DRR uptake. However, there are gaps in coverage for some regions, sectors, and hazards that require attention. There are DRR coverage gaps in Europe and Central Asia and the Middle East and North Africa for all serious hazards. Also, while the World Bank is conducting analytical work on the needs of disaster vulnerable groups, there has been slow progress on incorporating their needs into operations. There are also missed opportunities to use conflict-sensitive approaches to mitigate conflict risks and pursue peace-building. Also, the Bank’s frequent inability to demonstrate the effects of its DRR activities on reduced exposure and vulnerability has consequences on its ability to make a development case for risk reduction. Most DRR operations are not providing sufficient information to establish the level of DRR being achieved, inhibiting an understanding of how DRR contributes to development impacts, such as reduced economic loss and mortality. IEG offers the World Bank four recommendations to improve their performance on disaster risk reduction: (i) Incorporate DRR activities in regions and sectors and for hazards that exhibit significant coverage gaps. (ii) Identify and measure the effects of DRR activities on exposure and vulnerability to strengthen the development case for clients facing serious disaster risks. (iii) Integrate the needs of populations disproportionately vulnerable to disasters caused by natural hazards into DRR project targeting and design, implementation, and results reporting. (iv) In countries affected by serious natural hazards and fragility and conflict risks, identify and assess the ways in which hazards and conflict interrelate and use this to inform country engagement and project design.